ALTERNATIVE ENERGY IN A SPAGHETTI WESTERN: CLINT EASTWOOD CONFRONTS STATE RENEWABLE ENERGY POLICY (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
The legal structure in a given country affects the mechanisms through which that country can promote renewable power technologies. Federalist forms of government denote a system in which political sovereignty is constitutionally divided between a central federal authority and constituent states or provinces. Such federalist forms of government describe several large and established countries, such as the United States, Germany, India, Australia, Brazil, Canada, Malaysia, Mexico, Nigeria, and Switzerland. Renewable energy policy at the state level, in countries with a federalist form of government, can be complex and varied. The importance of the electric sector in the modern industrial economy is reflected in its changing role and unique societal impacts. First, energy is a unique force in the universe. Energy is the signature technology of the modern era, which comprises the last 300 years of the several million years of human life on the planet. Second, electricity, unlike all other forms of energy, cannot be efficiently stored in bulk for more than a second before it is lost as waste heat.  Therefore, the supply of electricity must match the demand for electricity over the centralized utility grid of a nation on an instantaneous basis, or else the electric system shuts down or expensive equipment is damaged. This unique role and character have legal facets that states have not always comprehended clearly. Renewable initiatives implemented recently at the state level in the United States are confronting Constitutional challenges. The implementation of renewable energy policy in the U.S. has been a bit like a Sergio Leone spaghetti western, “The Good, the Bad, and the Ugly.” It is still not determined how precisely the legal plot will end. The U.S. Constitution and federalism play a significant role in determining the outcome.